2003
DOI: 10.1007/s00266-003-0109-7
|View full text |Cite
|
Sign up to set email alerts
|

Natural-Looking Umbilicus as an Important Part of Abdominoplasty

Abstract: The umbilicus is an important and essential aesthetic component of the abdomen. Many surgeons use different methods to relocate umbilicus during abdominoplasties. We prefer to use a simple combination of different well-known principles to form the neo-umbilicus. The main steps of the procedure are to make an elliptical vertical incision, to do vertical abdominal fascial plication, to embed the umbilical stalk in this plication by suturing the umbilical skin and the rectus fascia together to maintain the umbili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 11 publications
0
13
0
6
Order By: Relevance
“…Although most surgeons extend a midline incision around the umbilicus, it has been shown that cutting through the umbilicus has no disadvantage and is superior cosmetically 6 . We chose to incise through the umbilicus, not only for these reasons, but also because it offers a direct approach and excellent exposure of the pathology, especially if meticulous hemostasis is ensured using diathermy.…”
Section: Discussionmentioning
confidence: 99%
“…Although most surgeons extend a midline incision around the umbilicus, it has been shown that cutting through the umbilicus has no disadvantage and is superior cosmetically 6 . We chose to incise through the umbilicus, not only for these reasons, but also because it offers a direct approach and excellent exposure of the pathology, especially if meticulous hemostasis is ensured using diathermy.…”
Section: Discussionmentioning
confidence: 99%
“…Es preciso establecer que tan importante resulta reconocer la tétrada que deforma la pared abdominal que bien describe el autor, como también realizar una buena preparación preoperatoria que al final determinará la ocurrencia o no de complicaciones y sobre todo, de aquellas relacionadas con los cambios en los valores de hematocrito y de hemoglobina, además de los trastornos provocados por una gran plicatura de los rectos y su consecuente síndro-me de comportamiento intraabdominal, que pueden ser prevenidos (1).…”
Section: Gráficaunclassified
“…El ombligo es un importante componente estético del abdomen (1,2). Las deformidades de esta pared son frecuentes en nuestro medio, causan serios trastornos estéticos, funcionales y psicológicos y además constituyen motivo de consulta en los Servicios de Cirugía Plástica por parte de los pacientes que la padecen (3).…”
Section: Introductionunclassified
“…Many different techniques have been described on how to create the naturalappearing umbilicus, but most agree on the similar traits necessary to achieve the desired aesthetic result. [1][2][3] Other than the appropriate height and midline location of the umbilicus, important features of the aesthetically pleasing umbilicus are small size, inverted T or vertical shape, retrusion ("inny" versus "outy"), superior hooding, and a natural abdominal wall periumbilical concavity necessary for a smooth transition between the abdominal wall and the umbilicus. Potential adverse effects of surgery that we try to minimize are an overt or cicatricial scar.…”
mentioning
confidence: 99%